Endoscopic resection of gastric gastrointestinal stromal tumor using clip-and-cut endoscopic full-thickness resection: a single-center, retrospective cohort in Korea - Yuri Kim; Ji Yong Ahn; Hwoon-Yong Jung; Seokin Kang; Ho June Song; Kee Don Choi; Do Hoon Kim; Jeong Hoon Lee; Hee Kyong Na; Young Soo Park (Korean Society of Gastrointestinal Endoscopy, 2024)
Background/Aims To overcome the technical limitations of classic endoscopic resection for gastric gastrointestinal stromal tumors (GISTs), various methods have been developed. In this study, we examined the role and feasibility of clip-and-cut procedures (clip-and-cut endoscopic full-thickness resection [cc-EFTR]) for gastric GISTs. Methods Medical records of 83 patients diagnosed with GISTs after endoscopic resection between 2005 and 2021 were retrospectively reviewed. Moreover, clinical characteristics and outcomes were analyzed. Results Endoscopic submucosal dissection (ESD) and cc-EFTR were performed in 51 and 32 patients, respectively. The GISTs were detected in the upper third of the stomach for ESD (52.9%) and cc-EFTR (90.6%). Within the cc-EFTR group, a majority of GISTs were located in the deep muscularis propria or serosal layer, accounting for 96.9%, as opposed to those in the ESD group (45.1%). The R0 resection rates were 51.0% and 84.4% in the ESD and cc-EFTR groups, respectively. Seven (8.4%) patients required surgical treatment (six patients underwent ESD and one underwent cc-EFTR,) due to residual tumor (n=5) and post-procedure adverse events (n=2). Patients undergoing R0 or R1 resection did not experience recurrence during a median 14-month follow-up period, except for one patient in the ESD group. Conclusions cc-EFTR displayed a high R0 resection rate; therefore, it is a safe and effective therapeutic option for small gastric GISTs.